2014
DOI: 10.18632/oncotarget.2261
|View full text |Cite
|
Sign up to set email alerts
|

The anti-apoptotic BAG3 protein is expressed in lung carcinomas and regulates small cell lung carcinoma (SCLC) tumor growth

Abstract: BAG3, member the HSP70 co-chaperones family, has been shown to play a relevant role in the survival, growth and invasiveness of different tumor types. In this study, we investigate the expression of BAG3 in 66 specimens from different lung tumors and the role of this protein in small cell lung cancer (SCLC) tumor growth. Normal lung tissue did not express BAG3 while we detected the expression of BAG3 by immunohistochemistry in all the 13 squamous cell carcinomas, 13 adenocarcinomas and 4 large cell carcinomas.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 19 publications
(33 reference statements)
1
32
0
Order By: Relevance
“…The BAG3 gene is a transcriptional target of the stress-induced transcription factor HSF1 which was found to be upregulated in glioma (44). In addition to glioblastoma, overexpression of BAG3 has been observed in different types of tumors including pancreatic carcinoma, leukemia, small cell lung cancer, and thyroid carcinoma, compared with very low basal levels of BAG3 in non-malignant cells (20,21,(45)(46)(47). The role of BAG3 in promoting cell survival may therefore enhance therapy resistance in glioblastoma and several other human neoplasms.…”
Section: Discussionmentioning
confidence: 99%
“…The BAG3 gene is a transcriptional target of the stress-induced transcription factor HSF1 which was found to be upregulated in glioma (44). In addition to glioblastoma, overexpression of BAG3 has been observed in different types of tumors including pancreatic carcinoma, leukemia, small cell lung cancer, and thyroid carcinoma, compared with very low basal levels of BAG3 in non-malignant cells (20,21,(45)(46)(47). The role of BAG3 in promoting cell survival may therefore enhance therapy resistance in glioblastoma and several other human neoplasms.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, BAG3 expression is increased in a large number of cancers including: acute lymphocytic and B cell chronic lymphocytic leukemia [52, 53] thyroid carcinoma [54]; melanomas [55] non-small-cell lung cancer [56]; hepatocellular carcinoma [57]; pancreatic adenocarcinoma [58], small cell carcinoma of the lung [59] and glioblastoma [60]. The overexpression of BAG3 in malignant cells increased motility and metastasis, whereas reduction in BAG3 protein by RNA interference decreased cell motility.…”
Section: Bag3 Mutants Myofibrillar Myopathy and Dilated Cardiomyopathymentioning
confidence: 99%
“…In addition to the BAG domain, BAG3 contains a WW domain near its N-terminus and a proline-rich region (multiple PXXP motifs) (16,17), and our earlier study showed that BAG3 also regulates cell motility and tumor growth, invasion and metastasis (18). Moreover, several lines of evidence indicate that downregulation of BAG3 enhances chemotherapy-mediated apoptosis among cancer cells (19)(20)(21), which is consistent with the recent finding that BAG3 stabilizes Mcl-1, Bcl-2 and Bcl-X L , thereby promoting cancer cell survival (22,23). The precise mechanism by which BAG3 exerts these effects remains unclear.…”
Section: Introductionmentioning
confidence: 99%